Efficacy of Albendazole and Mebendazole Against Soil Transmitted Infections among Pre-School and School Age Children: A Systematic Review and Meta-Analysis - Temesgen Bekele; Lata Lachisa; Arega Tsegaye; Ketema Bacha; Tsige Ketema (Springer, 2024)
Abstract Background Soil-transmitted helminthic (STH) infections are the leading cause of stunting among children. To lessen the burden, the World Health Organization (WHO) recommended a periodic deworming program through the use of single-dose therapy in the endemic regions. Therefore, the purpose of this study was to synthesize evidence about the efficacy of anthelminthic drugs against STH infections among preschool and school-age children. Methods The Preferred Reposting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria were followed in this study. Relevant electronic databases, including PubMed, Scopus, Embase, DOAJ, Science Direct, the WHO Clinical Trials.gov library, Google Scholar, and AJOL databases, were searched for relevant publications. Randomized controlled trials (RCTs) and non-randomized interventional studies focused on the efficacy of albendazole and mebendazole against STHs in children were included in the study. Review Manager was used to analyze the data. A random effects model was used to obtain the pooled estimated efficacy. To evaluate heterogeneity, the I 2 test and Cochrane Q (χ2) were employed. The risk of publication bias was investigated using Egger's test and the funnel plot. The protocol of this review was registered at the PROSPERO international prospective register of systematic reviews (CRD42023401196). Results Of the 69 publications selected for the systematic review, 66 with complete data were included in the meta-analysis. Single doses of albendazole and mebendazole have shown satisfactory efficacy [egg reduction rate (ERR)] against Ascaris lumbricoides [95.54% (95% CI: 88.75-102.34%) and 98.69% (95% CI: 97.68-99.65%), respectively. The effectiveness of these two drugs against Trichuris trichiura and hookworms was comparatively low (< 80% ERR), except for albendazole, which showed high ERRs [93.44% (95%CI: 92.39-94.49%)] against hookworms. The cure rate (CR) of albendazole against T. trichiura, A. lumbricoides, and hookworms were 50.8%, 91.3%, and 78.32%, respectively. Likewise, mebendazole showed CRs of 48.15%, 92.8%, and 49.32% against T. trichiura, A. lumbricoides, and hookworms, respectively. Subgroups such as studies conducted after 2000, diagnostic type (McMaster), and longer follow-up weeks significantly reduced the efficacy of the two drugs against T. trichura. While the combination of albendazole or mebendazole with other drugs and RCT showed significantly improved efficacy against T. trichura. The count of eggs per gram of stool (EPG) was identified as one of the variables that negatively and significantly influenced the efficacy of albendazole or mebendazole against A. lumbricoides. Conclusion Despite the wide range of ERRs and CR reported in the different articles included in this review, the pooled estimated efficacy of albendazole and mebendazole against STHs falls in the satisfactory category of WHO recommendations. Further evaluation of the combination of anthelminthic drugs as a preventive chemotherapy option and routine drug efficacy testing are necessary to prevent the emergence and widespread use of drug-resistant STHs.